The Mapping of Intellectual Property in Animation Film for Copyright - Miyosa, Septa (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
Animated films have various assets and products. The principle in the creative economy is to protect and empower each asset for business purposes. The problem that arises is how to map assets in animated films so that they are eligible to be registered for copyright protection. The purpose of the study is to map assets in an animated production for copyright protection. The research method is qualitative descriptive and literature study to map assets in animated films. The discussion shows that animated films can be mapped based on ideas and concepts that appear in assets and products. Assets are the values ​​contained in a product, while products are the embodiment of concepts. Assets are in the form of story ideas, synopses, loglines. Products are in the form of scripts, character designs, audio. The conclusion shows that assets and products are intellectual property so they need to be protected by their creators as a form of empowerment of the creative economy.